Exploring the prebiotic potential of xanthan gum and its modified forms for the production of synbiotic yogurt. Issue 11 (1st September 2022) - Khalid, Nazia; Ramzan, Rabia; Zahoor, Tahir; Muhammad, Zafarullah; Tehseen, Saima; Aziz, Mahwash; Batool, Rizwana
Abstract: Crude xanthan gum was hydrolyzed using acid (HCl), base (NaOH), and enzyme (cellulase). Synbiotic yogurt was developed with the addition of xanthan gum and its hydrolyzed forms (0.1, 0.5, and 1% [w/v]) as prebiotic along with probiotics ( Bifidobacterium longum BB536). Fat, protein, lactose, total solid contents, pH, and viscosity decreased, whereas syneresis and acidity were increased during the storage period of 28 days. The addition of hydrolyzed xanthan gum as prebiotic proved to be the best for enhancing the viability of yogurt culture and probiotics maintaining the viable count of the B. longum BB536 above 6 Log CFU/g during storage with maximum count of 7.898 Log CFU/g in yogurt containing 1% of enzyme hydrolyzed xanthan gum (EHXG). The addition of EHXG beyond this limit disturbed the final texture of yogurt due to phase separation. Hence, hydrolyzed xanthan gum can be the best candidates as prebiotics to be added in yogurt. Practical applications: The finding of the present study is beneficiary from the industrial point of view in order to develop the versatile dairy products having valuable influence on human health that provide healthy gut functions with a balance between good and bad bacteria. The use of prebiotics from microbial sources (xanthan gum) will serve as a sustainable, fast, and cheaper source and can be obtained even from waste. The study will have a good economic impact when executed in the form of commercial synbiotic food products.